Social disparities producing health inequities and shaping sickle cell disorder in Brazil - Clarice Santos Mota; Karl Atkin; Leny Alves Bomfim Trad; Ana Luisa A. Dias (2017)
Sickle cell disorder (SCD) is a severe recessive genetic condition manifesting in several complex forms. It is a cause of high mortality rates across the world, affecting predominantly non-white populations. This article aims to discuss how persistent social disparities and health inequalities in the Brazilian context can produce negative effects in lifelong conditions such as Sickle Cell Disorder. Appearing usually in the patient's first year of life, when not treated, SCD may lead to several life threatening complications and impact on a person's quality of life. In order to understand the link between health and social circumstances, it is important to consider the socio-economic transformation of Brazilian society over time, as well as cultural and historical aspects of the country. The concept of inequity will ground this analysis, facilitating an understanding of the process of producing an extra burden for people with SCD as a result of social disparities, including the existence of racism.